Vertical Profiles Of Chlorophyl-a In The Tanjung Putus Oxbow Buluh China Village Siak Hulu Sub District Kampar District Riau Province - Leonardo Windra Sinurat; Madju Siagian; Asmika Simarmata (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted of March 2013 in the Tanjung Putus Oxbowthat is located in the Buluh China Village. This research aims to understand thevertical profil chlorophyl-a.Chlorophyl-a samples were collected from 3 stations. In each stations,there are 2 sampling sites, in the surface and 2,5 depth. Sampling was done threetimes, once a week. Result shown that the chlorophyl-a content ranged from 8,97-20,1 g/l. Water quality parameters values were: depth : 89,0–92,3 cm;temperature: 30 –31 oC; transparency: 141–301,7 cm; pH: 5; DO: 3,67 – 6,17mg/l; CO2: 7,76–15,7 mg/l; phosphate: 0,04– 0,13 mg/l and nitrate: 0,02 – 0,100mg/l. Chlorophyl-a was higher in the surface tahan of secchi area. The resultshowed that Tanjung Putus Lake water is enough productive and be support theorganism aquatic.Key words : Chlorophyl-a, the vertical profiles, Tanjung Putus Oxbow